A novel framework for conditional simulation of fully nonstationary spatially varying ground motion field. (2nd September 2020) - Rodda, Gopala Krishna; Basu, Dhiman
Summary: Existing procedures for conditionally generating the spatially varying ground motion (SVGM) through the coherency‐based methods can be broadly categorized into two approaches: (i) cross‐spectral density (CSD)‐based procedures and (ii) auto‐spectral density (ASD)‐based procedures (reported by the authors elsewhere). CSD‐based procedures consider only the phase variability, whereas ASD‐based procedures account for phase as well as the amplitude variability. However, the ASD‐based framework and most of the CSD‐based frameworks simulate the stationary SVGM, and nonstationarity is imparted through the uniform modulation, ignoring the temporal variation of the frequency content. This paper proposes an evolutionary power spectral density (EPSD)‐based framework for the simulation of nonstationary SVGM. This framework is developed in two steps. First, a new methodology based on Hilbert transform is proposed to compute the nonstationary ground motion given the EPSD, modulating functions, and phase. Second, the ASD‐based framework reported by authors elsewhere is extended to account for the EPSD, and the associated nonstationary ground motion is simulated using the proposed methodology. Nonstationary ground motions thus simulated are assessed against SMART1 array recordings. The close resemblance between the simulated accelerogram and the recorded data indicates that the proposed EPSD based framework accounts not only for the phase and amplitude variabilities but also for the nonstationarity.